Increased serum 1,25-dihydroxyvitamin D levels in gynecologic cancer patients with Post-Acute-Covid-Sequela (PASC)/Long COVID - Stefania Bellone; Eric E. Siegel; Alessandro D. Santin (Elsevier, 2023)
Post-acute sequelae of COVID-19 (PASC), also known as Long-Covid (LC), may affect 10-30 % of COVID-infected patients, and is characterized by a variety of debilitating symptoms lasting over 3 months after the acute infection, including but not limited to dyspnea, fatigue, and musculoskeletal, cognitive, and/or mental health impairments. Vitamin D is an essential nutrient primarily recognized for its role in regulating calcium and bone health but also endowed with potent anti-inflammatory activity affecting a variety of immune cells. We retrospectively evaluated the plasmatic levels of both 1,25-dihydroxyvitamin-D (1,25 OH), and 25-hydroxyvitamin-D (25 OH), the active and storage forms of vitamin-D3, respectively, in the serum of gynecologic cancer patients affected by PASC/LC vs control cancer patients. We found elevated 1,25-dihydroxyvitamin-D levels in 5 out of 5 of the PASC/LC patients (mean ± SD = 97.2 ± 26.9 pg/mL) versus 0 out of 10 of randomly selected cancer control patients (44.9 ± 17.2 pg/mL, p = 0.0005). In contrast, no significant difference was noted in the levels of 25-dihydroxyvitamin-D in PASC/LC (mean ± SD = 48.2 ± 15.8 ng/mL) versus controls (43.0 ± 11.6 ng/mL, p = 0.48). Importantly, abnormal levels of vitamin D were found to persist for at least 2 years in patients with long covid symptoms. The active form (1,25OH) but not the storage form (25 OH) of vitamin-D is significantly elevated in PASC/LC cancer patients. Abnormally and persistently elevated 1,25OH levels, similarly to sarcoidosis patients, may represent the results of extrarenal conversion of vitamin D by activated macrophages, and a novel biomarker of persistent inflammation in gynecologic cancer patients with PASC/LC.